A Spatio-Temporal Groundwater Fluoride Contamination Assessment to Infer the Hydro-geochemical Analysis of Punjab Satluj Floodplain - Harsimrat, K. (Journal of Scientific Research, 2024)
Punjab Satluj Floodplain is a Hydro-geologically, ecologically, and economically very precious resource-rich landscape. This area is fragile due to flood risk; since its inception, it has attracted lots of economic and sociocultural activities that adversely affect hydro-geochemical conditions. Spatial and statistical analysis of land use and land cover change reveals that from 1975 to 2011, this landscape experienced 56.55 % land use and land cover transformation. Maximum transformation is noticed in the agricultural and built-up areas. In 1975, agricultural and built-up areas covered 47057.11 hectares (45.13 %) and 469.5 hectares (0.45 %), respectively, of the Punjab Satluj floodplain, which was expanded and covered 91011.36 hectares (87.28 %) and 6495.7 hectares (6.24 %) respectively in 2011. Adversities of these values can be estimated from the groundwater contamination analysis that reveals the specific electrical conductance (EC), nitrate (NO3), potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), and fluoride (F) contamination in the water exceed its permissible consumption limits and effects ecological health. The present research work is the epigram of the hydrogeochemical condition of the Punjab Satluj floodplain concerning the spatial distribution of fluoride contamination and its proximate causes.